2014
DOI: 10.1016/j.pain.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Biased agonism of the μ-opioid receptor by TRV130 increases analgesia and reduces on-target adverse effects versus morphine: A randomized, double-blind, placebo-controlled, crossover study in healthy volunteers

Abstract: Opioids provide powerful analgesia but also efficacy-limiting adverse effects, including severe nausea, vomiting, and respiratory depression, by activating μ-opioid receptors. Preclinical models suggest that differential activation of signaling pathways downstream of these receptors dissociates analgesia from adverse effects; however, this has not yet translated to a treatment with an improved therapeutic index. Thirty healthy men received single intravenous injections of the biased ligand TRV130 (1.5, 3, or 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 232 publications
(230 citation statements)
references
References 30 publications
10
217
1
2
Order By: Relevance
“…This compound, factor of 3-fold for G protein over arrestin signaling), yet the authors reported a favorable separation between analgesic efficacy and gastrointestinal and respiratory side effects when tested in rodent models (Dewire et al, 2013). Currently in clinical trials, TRV-130 has proven to be a very potent analgesic in humans (Soergel et al, 2014). However, the results of the phase II clinical trial have not revealed a significant reduction in side effects, raising the question of whether biased agonists at MOR can dissociate analgesia from respiratory depression/constipation or if a greater degree of bias is necessary to translate into human therapeutic responses.…”
Section: Translating Biasmentioning
confidence: 99%
“…This compound, factor of 3-fold for G protein over arrestin signaling), yet the authors reported a favorable separation between analgesic efficacy and gastrointestinal and respiratory side effects when tested in rodent models (Dewire et al, 2013). Currently in clinical trials, TRV-130 has proven to be a very potent analgesic in humans (Soergel et al, 2014). However, the results of the phase II clinical trial have not revealed a significant reduction in side effects, raising the question of whether biased agonists at MOR can dissociate analgesia from respiratory depression/constipation or if a greater degree of bias is necessary to translate into human therapeutic responses.…”
Section: Translating Biasmentioning
confidence: 99%
“…TRV-130 has also shown central opioid action, as demonstrated by marked pupillary constriction [Soergel et al 2014a]. Currently, TRV-130 is being evaluated in patients undergoing abdominoplasty and bunionectomy [ClinicalTrials.gov identifiers: NCT02100748, NCT02335294].…”
Section: Trv-130mentioning
confidence: 99%
“…Indeed, enhanced morphine analgesia with reduced respiratory and gastrointestinal side effects was reported in b-arr2 knockout mice (Bohn et al, 1999;Raehal et al, 2005;Maguma et al, 2012). Recently, ligands with impaired b-arr2 recruitment have been reported to provide potent analgesia with less severe side effects (Groer et al, 2007;DeWire et al, 2013;Soergel et al, 2014). However, the improved pharmacological profiles of these ligands may still be due to their partial agonism, with lower overall efficacy than morphine, rather than true "bias" away from b-arr2 recruitment (Thompson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%